Nuclear orientation of156Tb in gadolinium matrix - Říkovská, J; Machová, A; Hamilton, W; Dupák, J; Mo, C; Finger, M; Lebedev, N; Neganov, B; Pavlov, V; Shchus, A (Kluwer Academic Publishers, 1979)
The anisotropy of the angular distribution of gamma-rays from the decay of156Tb, oriented in a gadolinium matrix at low temperatures, has been measured at the angles of 0 and π/2 with respect to the applied magnetic field direction in the range of temperatures from 14·6 to 68·4 mK. The temperature dependence of anisotropy was measured for the first time. The parameters of hyperfine magnetic dipole and electric quadrupole splittings have been determined and the values of the magnetic dipole moment |Μ156|=(9·6±1·3)×10-27 J/T and the electric quadrupole moment Q156=(2·9±0·9)×10-28 m2 of the156Tb ground state have been calculated. Multipole mixing ratios and B(E2) branching ratios of many gamma-ray transitions occurring in156Gd have been found and the results have been discussed in terms of the rotational-vibration and pairing-plus-quadrupole models. © 1979 Academia, Publishing House of the Czechoslovak Academy of Sciences.